Azerbaijan - Axundov, Fuad, 1968-; Khalilov, Emil (Helsinki : Haydar Aliyev Foundation, 2010)
The Azerbaijan edition, herein presented was prepared with a view to providing detailed information regarding this country, also known as The Land of Fire. With more than thousand photos, the book aims at presenting the ancient history, culture, traditions and ethnographic peculiarities of Azerbaijan, as well as he country's past, present and modern image.
Keywords: Architecture -- Azerbaijan -- Pictorial works; Azerbaijan -- Pictorial works